PELATIHAN PEMBUATAN SABUN CUCI ANTIBAKTERI BERBASIS HERBAL DAUN TEH HIJAU PADA SISWA DAN GURU SEKOLAH INDONESIA DAVAO. DAVAO CITY, PHILIPINA - Utami, Dwi; Akrom, Akrom; Pertiwi , Deasy Vanda; Nafiah, Mufidatun; Hartati, Meity; Antonius, Rosanio; Ardiyanto, Restu; Suryo Putro, Nur Fitriansyah (Jurnal Bakti untuk Negeri, 2025)
Tea leaves and betel leaves are among the abundant local resources in the Davao region, Davao City, Philippines, that have not been optimally utilized. This community service aims to improve the knowledge and skills of students at the Indonesian School in Davao in making herbal dish soap from tea leaves. This activity was conducted using a training and hands-on practice method for 45 students and teachers. Training material on the benefits of tea leaves as a natural ingredient in dish soap and how to make it. The results of the service show an increase in knowledge, from 30% before training to 68.57%. A total of 85% of participants were able to make green tea dish soap after attending the training, compared to 45% previously. Students were able to understand the process of making herbal dish soap from tea leaves and apply it in their daily lives. This community service can make a positive contribution to society and the surrounding environment. This activity is also an example of integrating knowledge and skills about creating natural and environmentally friendly products into the school curriculum.